2017
DOI: 10.4236/oalib.1103721
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the Implementation of the Nursing Approach in Public Hospitals in Lubumbashi in the Democratic Republic of Congo: A Cross-Sectional Descriptive Study

Abstract: Introduction: The nursing approach (NA) is the essence of the nursing profession. However, its implementation is almost absent in the hospitals of the Democratic Republic of Congo (DRC). Objectives: The aim of this study was to determine nurses' knowledge, attitudes and practices in relation to the nursing approach and to identify barriers to the implementation of this approach. Methods: To achieve these objectives, we carried out a cross-sectional descriptive study among the nurses of the 11 public hospitals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 1 publication
0
17
0
Order By: Relevance
“…The copyright holder for this preprint (which was not this version posted October 8, 2019. . https://doi.org/10.1101/19008144 doi: medRxiv preprint instance, lack of theoretical and practical knowledge [20][21][22][23][24][25][26], institutional factors [6,11], professional factors [11],work overload [11,21,23,[25][26][27][28], lack of previous experience [6,27], inadequate nursing staff [20], patients with complicated case [24], working in a hospital [25], patient economic status [25], early discharge [25,26], not cooperative [25], lack of training [6,18,22,26,29], low educational status [27,28], poor Nurses skill [28], lack of time [18,20,27,30], lack of authorities' support [27] and lack of equipment and material [20,27,28], were some of the factors associated with implementation of nursing process. On the contrary, a study conducted in Nigeria shows that institutional factor does not pose a barrier to the use of nursing process [...…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint (which was not this version posted October 8, 2019. . https://doi.org/10.1101/19008144 doi: medRxiv preprint instance, lack of theoretical and practical knowledge [20][21][22][23][24][25][26], institutional factors [6,11], professional factors [11],work overload [11,21,23,[25][26][27][28], lack of previous experience [6,27], inadequate nursing staff [20], patients with complicated case [24], working in a hospital [25], patient economic status [25], early discharge [25,26], not cooperative [25], lack of training [6,18,22,26,29], low educational status [27,28], poor Nurses skill [28], lack of time [18,20,27,30], lack of authorities' support [27] and lack of equipment and material [20,27,28], were some of the factors associated with implementation of nursing process. On the contrary, a study conducted in Nigeria shows that institutional factor does not pose a barrier to the use of nursing process [...…”
Section: Introductionmentioning
confidence: 99%
“…61.1 % participants reported that they are not being able to follow patients because of low nurse inadequate nurse patient ratio. 32.4 % participants reported that there are administration related barriers for the execution of nursing process (Julie et al, 2017). Adeyemo & Olaogun (2013) observed that 67.6% of respondents' were agreed upon numerous resources related barriers, which included insufficient staff in the unit, lack of specified nursing care document and educational budget, insufficient equipment and absence of supplies and materials that are required for the execution of nursing process (Adeyemo & Olaogun, 2013).…”
Section: Nursing Processmentioning
confidence: 99%
“…Afolayan, Donald et al (2013) defined factors that influence the implementation of the nursing approach were found that (25.6%) participants reported the barrier related to nursing process and (61.8%) participants response to have inadequate equipment that are required to execute the nursing process, (63.4%), respondents' report lack of time for application of nursing process (Afolayan, Donald, Baldwin, Onasoga, & Babafemi, 2013). In another study according to Julie et al (2017) revealed that 70.2 % participants' answer that hospital administration needs to be enlightened on the benefits of nursing process. 61.1 % participants reported that they are not being able to follow patients because of low nurse inadequate nurse patient ratio.…”
Section: Nursing Processmentioning
confidence: 99%
See 2 more Smart Citations